Regulation of Intestinal Inflammation by Dietary Fats - Basson, Abigail R.; Chen, Christy; Sagl, Filip; Trotter, Ashley; Bederman, Ilya; Gomez-Nguyen, Adrian; Sundrud, Mark S.; Ilic, Sanja; Cominelli, Fabio; Rodriguez-Palacios, Alex (Frontiers in Immunology, 2021)
With the epidemic of human obesity, dietary fats have increasingly become a focal point of biomedical research. Epidemiological studies indicate that high-fat diets (HFDs), especially those rich in long-chain saturated fatty acids (e.g., Western Diet, National Health Examination survey; NHANES ‘What We Eat in America’ report) have multi-organ pro-inflammatory effects. Experimental studies have confirmed some of these disease associations, and have begun to elaborate mechanisms of disease induction. However, many of the observed effects from epidemiological studies appear to be an over-simplification of the mechanistic complexity that depends on dynamic interactions between the host, the particular fatty acid, and the rather personalized genetics and variability of the gut microbiota. Of interest, experimental studies have shown that certain saturated fats (e.g., lauric and myristic fatty acid-rich coconut oil) could exert the opposite effect; that is, desirable anti-inflammatory and protective mechanisms promoting gut health by unanticipated pathways. Owing to the experimental advantages of laboratory animals for the study of mechanisms under well-controlled dietary settings, we focus this review on the current understanding of how dietary fatty acids impact intestinal biology. We center this discussion on studies from mice and rats, with validation in cell culture systems or human studies. We provide a scoping overview of the most studied diseases mechanisms associated with the induction or prevention of Inflammatory Bowel Disease in rodent models relevant to Crohn’s Disease and Ulcerative Colitis after feeding either high-fat diet (HFD) or feed containing specific fatty acid or other target dietary molecule. Finally, we provide a general outlook on areas that have been largely or scarcely studied, and assess the effects of HFDs on acute and chronic forms of intestinal inflammation.